Outcome of the Thai Traditional Medicine Service - Sawadichai, Chatchai; Chaicharoenpong, Kulwan; Sookphaisarn, Wassana; Sanguansap, Pensri; Jamsat, Udomluk; Wanvijitr, Chantana; HomCharoen, Kesarindra; Samranjit, Janya; Noptanaphatra, Keawjai; Kittisartra, Suchanthip; Jetcharoenarraya, Pimyada; Singnoi, Sutathip; et al. (Journal of Health Science of Thailand, 2018)
The objectives of this descriptive research were to studied outcomes of Thai Traditional Medicine services and opinions among persons that related services in Prapokklao hospital, Chanthaburi province. The data collection derived from in-depth interviews in 14 persons related to Thai Traditional Medicine Services (hospital’s director, physicians, nurses, traditional medical practicioners and health volunteers) and questionnaires in 623 responders (patients and relatives). It was reported that the clients found the environment of the service area suitable and accomodating. On input issue, the policy was clear; caregivers showed positive attitude supportive allowed patients to exercise their rights and preferences. Other supporting factors included adequate herbal drug regimens and one-stop service set up. On process, services were found to be convenient, accessible, and could be well integrated into the exiting health system. High level of satisfaction was reported by their clients (92.10%) while 5.78 percent of them proclaimed cured, 36.78 percent improved, 3.65 percent stable and 53 percent loss in follow-up. All above results indicate that the Thai Traditional Medicine Services should be expanded to all hospitals and health centers in Chanthaburi province.